The Influence of Price and Store Atmosphere on Cafe Customer Satisfaction in Bengkalis (Case Study at Bikin Betah Cafe) - Wilda Niati (Politeknik Negeri Bengkalis, 2021)
The objective of this study was to determine the influence of price and store atmosphere on customer satisfaction. The study was faced at Bikin Betah Cafe Bengkalis in May until June 2020. The population of the research were customers with unknown and unlimited numbers in Bikin Betah Cafe. There were 100 respondents from Bengkalis who have visited Bikin Betah Cafe. The data was collected using an online questionnaire and purposive sampling. Data analysis method used desctiptive statistic and multiple linear regression by doing F Test and t test. According to the research results, all hypotheses have a positive and significant influence on customer satisfaction. Price and store atmosphere, together or partially, have a positive and significant effect on customer satisfaction.